Pengaruh Penggunaan Keywords Pada Penamaan Listing Airbnb Terhadap Tingkat Popularitas Di Kota Bangkok - Andy Hermawan; Fatika Rahma Sanjaya; Gregorius Aldo Primantono; Muhammad Syahirul Alim (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This study aims to explore the impact of keyword usage in Airbnb listing names on their popularity in Bangkok. Using regular expression (re) and tokenization methods, we identified the top 100 keywords from the listing name column. These keywords were then categorized based on business knowledge. Subsequently, the relationship between keyword usage and popularity was analyzed using the chi-square test, with popularity measured by the number of reviews in the last 12 months. The data used were sourced from Open Data Airbnb and underwent data cleaning and exploratory data analysis (EDA). The results of this study are expected to provide insights for Airbnb hosts to enhance the appeal of their listings through effective naming strategies.